Lsh, a modulator of CpG methylation, is crucial for normal histone methylation - Yan, Qingsheng (Oxford University Press, 2003)
Methylation of histone tails and CpG methylation are involved in determining heterochromatin structure, but their cause and effect relationship has not been resolved as yet in mammals. Here we report that Lsh, a member of the SNF2 chromatin remodeling family, controls both types of epigenetic modifications. Lsh has been shown to be associated with pericentromeric heterochromatin and to be required for normal CpG methylation at pericentromeric sequences. Loss of Lsh, in Lsh-deficient mice, results in accumulation of di- and tri-methylated histone 3 at lysine 4 (H3-K4me) at pericentromeric DNA and other repetitive sequences. In contrast, di- or tri-methylation of H3-K9 and distribution of HP1 appear unchanged after Lsh deletion, suggesting independent regulatory mechanisms for H3-K4 or K9 methylation. Experimental DNA demethylation with 5′-azacytidine results in a similar increase of H3-K4me. These results support the model that loss of CpG methylation caused by Lsh deficiency antecedes elevation of H3-K4me. Thus, Lsh is crucial for the formation of normal heterochromatin, implying a functional role for Lsh in the regulation of transcription and mitosis.